2020
DOI: 10.3390/polym12010149
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for Starve Fed/Flood Fed Single Screw Extrusion of Polymeric Materials

Abstract: A novel computer optimization system for flood fed/starve fed single screw extrusion of polymeric materials has been developed. This coupled system allows us to optimize single screw extrusion both flood fed and starve fed. Optimization is based on process simulation which is performed using global extrusion model GSEM (Global Screw Extrusion Model). The process is optimized with the use of GASEO (Genetic Algorithms Screw Extrusion Optimization) procedures which were developed using Genetic Algorithms. An exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
0
22
0
2
Order By: Relevance
“…In addition, the processing advantages like limited die pressure fluctuations and a lower specific power consumption by starve-fed mode have been studied [ 8 ]. An optimization model for starve-fed single-screw extrusion showed that the optimized mode in a single-screw extruder in terms of specific energy consumption is starve-fed mode [ 9 ]. Recently Mazzanti showed the improvement in mechanical properties of rubber-toughened wood composites through starve-fed extrusion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the processing advantages like limited die pressure fluctuations and a lower specific power consumption by starve-fed mode have been studied [ 8 ]. An optimization model for starve-fed single-screw extrusion showed that the optimized mode in a single-screw extruder in terms of specific energy consumption is starve-fed mode [ 9 ]. Recently Mazzanti showed the improvement in mechanical properties of rubber-toughened wood composites through starve-fed extrusion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chamil and colleagues developed an extruder melt temperature control with fuzzy logic [ 27 ]. Nastaj and Wilczynski in their work were able to optimize the single screw extrusion process using process simulations [ 28 ]. The process simulation technique was based on Genetic Algorithms Screw Extrusion Optimization procedures which have been developed using the Genetic Algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was used to optimize both the starve and flood fed screw extrusion. The authors were able to conclude that the starving fed extrusion is optimal with a high extrusion output and low energy consumption [ 28 ]. Bingol and some of his colleagues developed an ANN model to predict the load for lateral extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…They called this mechanism the "hybrid melting mechanism" (HMM). Wilczyński et al [22,23,27,32,[35][36][37] observed the same mechanism when processing polymer Simplified schematic drawing of the contiguous solids melting mechanism (CSM) in the flat screw channel, adopted and adapted from Gogos and Tadmor [6]. W is the channel width and X is the width of the solid bed.…”
Section: Introductionmentioning
confidence: 99%
“…Wilczyński et al [22,23,27,32,[35][36][37] reported, that in starve fed SSE the polymer mixture is melted much faster via the DSM mechanism. Furthermore, Wilczyński et al [23] noted that "a melting model considering the presence of two materials is not currently (2017) available" and proposes applying "simply-structured mixing rules" for the calculation.…”
Section: Introductionmentioning
confidence: 99%